2018
DOI: 10.1124/dmd.117.079871
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 Allelic Variants *34, *17-2, *17-3, and *53 and a Thr309Ala Mutant Display Altered Kinetics and NADPH Coupling in Metabolism of Bufuralol and Dextromethorphan and Altered Susceptibility to Inactivation by SCH 66712

Abstract: Metabolic phenotype can be affected by multiple factors, including allelic variation and interactions with inhibitors. Human CYP2D6 is responsible for approximately 20% of cytochrome P450-mediated drug metabolism but consists of more than 100 known variants; several variants are commonly found in the population, whereas others are quite rare. Four CYP2D6 allelic variants-three with a series of mutations distal to the active site (*34, *17-2, *17-3) and one ultra-metabolizer with mutations near the active site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Measurements of the enzymatic activity of allelic variant CYP2D6*53 have revealed increased metabolic rates towards bufuralol, dextromethorphan, and N-desmethyltamoxifen 3,6,7 . In contrast, a recent study reported a decrease in the clearance of primaquine 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of the enzymatic activity of allelic variant CYP2D6*53 have revealed increased metabolic rates towards bufuralol, dextromethorphan, and N-desmethyltamoxifen 3,6,7 . In contrast, a recent study reported a decrease in the clearance of primaquine 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Supersomes (Corning Life Sciences, Tewksbury, MA) were used in all assays except spectral binding titrations and stopped-flow spectroscopy. For spectral binding titrations and stopped-flow spectroscopy, purified CYP2D6 and CYP3A4 were used; expression and purification were as described elsewhere (Gillam et al, 1993(Gillam et al, , 1995Hanna et al, 2001;Glass et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were then centrifuged (16,100g) for 5 minutes, and 10 ml of the supernatant was injected onto a Waters Symmetry C18 column (5 mm, 3.9 Â 150 mm; Waters Corporation, Milford, MA) connected to a Waters e2965 high-performance liquid chromatography system paired with a Waters 2475 fluorescence detector. The instrument method and mobile phase were the same as previously described with bufuralol (Nagy et al, 2011;Glass et al, 2018). The 19-OH-bufuralol peak area was converted to concentration using a standard curve.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations